Topology design recommendations of transmission line towers to minimize the bolt slippage effect. (1st January 2019) - de Souza, Rafael Rodrigues; Fadel Miguel, Leandro Fleck; Kaminski, João; Lopez, Rafael Holdorf
Highlights: Topology design recommendations are able to decrease the bolt slippage effect. The investigated and recommended topologies are usually employed by the industry. Proposed scheme strongly reduces the number of possible tower configurations. The recommended topologies ensure a closer linear behavior and a lower tower weight. Abstract: Previous studies have recently demonstrated the importance of bolt slippage on the structural behavior of transmission line (TL) towers (CIGRE, 2009; Jiang et al., 2011; Ramalingam and Jayachandran, 2016; Jiang et al., 2017, just to name a few). In spite of these advances, this effect is still disregarded in the structural design, which is carried out through commercial computational packages that employ a linear or a geometrically nonlinear elastic analysis. Therefore, discrepancies between the model predictions and the actual tower behavior intrinsically occur. Moreover, its magnitude is highly dependent on the tower topology, a definition influenced by the engineer experience. Within this context, it is clear that the bolt slippage effect remains an open issue to treat on the engineering application point of view. Instead of including it in the mechanical model, a simpler alternative would be following a set of design topology recommendations able to minimize the connections' influence on structural tower behavior. Hence, starting from a FEM model that includes the nonlinear bolt slippage and fits the CIGRE (2009) experimental measurements, 72 models to the same self-supporting 230 kV real structure with small differences in their elements configurations are constructed. These topology variations include the most common features employed by the industry. Because the effect of each one of them is isolated and assessed separately (qualitatively and quantitatively), topology design recommendations are provided, allowing the structural behavior becomes considerably closer to the linear one. Finally, a critical appraisal of each variation choice on the impact of the final tower weight is carried out.